Webinar Peningkatan Literasi Demokrasi dan Literasi Informasi pada Media Bagi Generasi Muda - Mubaroq, Husni; Lailatul Fitria, Nurul Jannah (Lok Seva: Journal of Contemporary Community Service, 2023)
The younger generation is still reluctant to utilise their social media in democracy wise. Like the younger generation, they are still reluctant to get involved in politics, especially in the 2024 elections. Because of these problems, the service team organized community service activities by increasing democratic literacy and information literacy. To increase the understanding and skills of the younger generation in democratic literacy and information literacy on social media. So that partners understand not only entertainment and business content but also democracy and information education. The webinar event for the younger generation of Probolinggo City was attended by 30 partners. The implementation of events with democratic literacy and information literacy webinars is well organized and falls into the category of the right technique, right target, right time, and right purpose. As well as showing results according to the success target of program achievements. The results of monitoring and evaluation of the results of the closed questionnaire show that all partners strongly agree on this webinar event and that sustainable events can be held. The results of the open questionnaire showed that partners experienced changes and increased understanding and actions of partners related to democratic literacy and information literacy. In particular, partners are able and skilled in active democracy and the wise dissemination of political information on social media.